A cross-dimensional analysis of nanotechnology and equality: examining gender fairness and pro-poor potential in Canada's R&D landscape. Issue 3 (1st September 2020) - Ghiasi, Gita; Harsh, Matthew; Schiffauerova, Andrea
ABSTRACT: This study provides a cross-dimensional analysis of two equity concerns related to Canadian nanotechnology, investigating the relationship between the development of nanotechnology applications that benefit the poor and the gender gap in the scientific workforce. Many affluent countries, like Canada, aspire to use R&D to reduce inequality in both economic and gender dimensions, which makes cross-dimensional analyses essential for responsible innovation to fully understand how technologies affect equality and to guide policy. Relevant publications and patents are analyzed to explore if Canadian nanotechnology was addressing the needs of the poor and then to examine gender disparities in research and innovative advancements of pro-poor applications of nanotechnology. Only a small percentage of analyzed articles and patents reflected pro-poor priorities and Canadian workplaces involved in pro-poor nano-applications were largely male-dominated. Results suggest that coordination between pro-poor and gender-responsive policies is needed to promote both more equitable and more inclusive forms of innovation.